Observational study of fetomaternal outcome in pregnancy with COVID-19 infection - Dash, Pragyan; Padhi, Sobhan K.; Behera, Rabindra N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: According to World Health Organization (WHO) COVID-19 is declared as an infection of international health emergency on 11 March 2020. It is not clear whether clinical characteristics of pregnant women with COVID-19 infection differ from those of non-pregnant women and whether it aggravates its symptoms. Methods: This is a prospective observational study of 75 cases based on compiled clinical data of pregnant women with COVID-19 infection admitted to Hi-Tech Medical College from June 2020 to July 2021. All laboratory confirmed positive cases were included. Results: The most common symptoms reported was fever (24%) followed by myalgia, cough and shortness of breath, while 60% patients were asymptomatic. there were total 57 deliveries, out of which 46 were live birth. The incidence of preterm birth was 26.3%. Maternal mortality was maximum between 25-34 weeks of GA. 96.9% of new-born were tested for SARS CoV-2 and only 10 were found to be positive (17.5%). Conclusions: At present there is no evidence regarding increased risk of pregnant women succumbed to COVID-19 infection and experience severe pneumonia. The risk of preterm birth and spontaneous abortion not increased as reported in this study but shows possibilities of vertical transmission. COVID-19 infection in pregnancy with or without any comorbidities can cause complication to both mother and fetus irrespective of treatment. We aim to evaluate the association between SARS CoV-2 infection during pregnancy and adverse pregnancy outcomes.